Empowering comunity in creating business opportunities in Pahlawan Village, Batu Bara Regency - Sari , Dian Septiana; Irawan, I. (Universitas Muhammadiyah Malang, 2021)
The growth of small businesses plays an important role in the economic development of the community. Unfortunately, many regions are less able to develop small businesses even though their regions have various economic potentials. The purpose of this community service program was to empower rural communities in creating culinary business opportunities. This community service program was carried out by a team from the Universitas Pembangunan Panca Budi by involving the community in Pahlawan Village, Batu Bara Regency. The method used was through lectures and focus group discussions. The materials presented and discussed were business administration management and marketing management. Observation activities were carried out to evaluate the results of community service activities. The evaluation results show that the people in the Pahlawan Village need to develop alternative business strategies, improve business management, and identify various factors for marketing activities for culinary businesses.